2010
DOI: 10.1038/hdy.2010.130
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genetic variation and covariation in ejaculate traits reveal potential evolutionary constraints in guppies

Abstract: Ejaculates comprise multiple and potentially interacting traits that determine male fertility and sperm competitiveness. Consequently, selection on these traits is likely to be intense, but the efficacy of selection will depend critically on patterns of genetic variation and covariation underlying their expression. In this study, I provide a prospective quantitative genetic analysis of ejaculate traits in the guppy Poecilia reticulata, a highly promiscuous livebearing fish. I used a standard paternal half-sibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…Sperm head, tail and total lengths were all highly correlated and gave qualitatively similar results to one another in our subsequent analyses. Midpiece length was not highly correlated with the other measurements, corresponding to previous patterns reported for guppies (Evans, ). We therefore focus on midpiece and total length separately in our subsequent analyses (see Linear modelling ).…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Sperm head, tail and total lengths were all highly correlated and gave qualitatively similar results to one another in our subsequent analyses. Midpiece length was not highly correlated with the other measurements, corresponding to previous patterns reported for guppies (Evans, ). We therefore focus on midpiece and total length separately in our subsequent analyses (see Linear modelling ).…”
Section: Methodssupporting
confidence: 82%
“…); consistent with the output of our interaction models, no consistent patterns are evident. We note that our models should not be considered as independent: guppies exhibit complex genetic covariance among sexual behaviours, ornamentation and ejaculate traits that could constrain how sexually selected traits respond to inbreeding (Evans, , ; see Discussion). Finally, simpler HFC models run for each population and trait separately indicated no overall patterns at the population or trait level; only a few statistically significant HFCs were detected (the 95% CI excluded zero for 9 of 241 models [3.73%]; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, however, the remaining sperm traits assessed in this study (sperm morphology and velocity) did not predict sperm competitiveness. This is surprising as sperm viability is negatively genetically correlated with sperm morphology (head, flagellum and total length) in the study population (Evans, ). Yet, our finding is partially in keeping with recent work on guppies and other poeciliid fishes that did not find an effect of sperm morphology and only weak effects of sperm swimming speed on competitive fertilization success (Gasparini et al ., ; Boschetto et al ., ; Smith, ).…”
Section: Discussionmentioning
confidence: 89%
“…By comparing old and young ejaculates within the same male, and hence accounting for inter-male variability in sperm traits [13,15], we found that old sperm exhibited impaired sperm velocity compared with young sperm. As we did not use natural matings to manipulate sperm ageing, we were able to disentangle the effects of sperm ageing per se from variance attributable to mating history and male-female social interactions.…”
Section: Discussionmentioning
confidence: 99%